Implementasi Nilai-Nilai Moderasi Beragama dalam Menumbuhkan Sikap Toleransi Antar Umat Beragama - Ayu Andini; Ida Faridatul Hasanah; Chairul Amriyah (Jurnal Ilmiah Global Education, 2026)
This study aims to describe the implementation of religious moderation values and analyze how these values foster tolerance among students of different religions at SMKN 1 Bandar Lampung. This qualitative descriptive research employed observation, in-depth interviews, and documentation involving school leaders, Islamic Religious Education teachers, Civics teachers, Rohis instructors, Muslim students, non-Muslim students, and extracurricular participants. Data analysis used Miles and Huberman’s model consisting of data reduction, data display, and conclusion drawing. The results reveal that religious moderation values are integrated into school programs and learning practices, such as inclusive religious activities, mutual respect habituation, positive interreligious interactions, and school policies that emphasize harmony in diversity. Teachers play an active role as moderate role models and facilitators of dialogue spaces that help students understand differences positively. These findings confirm that religious moderation supports the creation of a harmonious school culture and strengthens tolerance among students.